Vocational Education Readiness in Preparing Green Jobs: Needs Analysis and Implementation Strategies - Feby Feby; Tian Havwini; Rusyda Nazhirah Yunus; Desi Ratna Sari; Windy Stefani; Nurul Fadilah; Luki Aswar; Multhahada Ramadhani Siregar (MASI Mandiri Edukasi, 2026)
The global transition toward a sustainable, low-carbon economy has significantly increased demand for green jobs, creating new challenges for vocational education institutions. However, many vocational curricula remain primarily oriented toward conventional industrial needs, raising concerns about their readiness to prepare graduates for green employment sectors. This study aims to analyze the readiness of vocational education, particularly at the polytechnic level, in preparing graduates for green jobs through a needs analysis and the development of implementation strategies. This research employed a mixed-method approach, combining qualitative and quantitative techniques. Data were collected through curriculum document analysis, questionnaires, interviews, and Focus Group Discussions (FGDs) involving lecturers, program representatives, and green job experts. The study focused on Batam State Polytechnic (Polibatam) as the research context. The findings indicate that vocational education readiness for green jobs remains at an emerging stage. Key gaps were identified in the integration of sustainability principles within institutional vision and mission statements, learning outcomes, curriculum content, teaching practices, lecturer competencies, and eco-friendly infrastructure. Although moderate alignment with industry collaboration and national policy frameworks was observed, the overall implementation of the curriculum remains fragmented. Based on expert validation through FGDs, this study proposes a prototype model for green curriculum integration that emphasizes institutional, curricular, instructional, and collaborative strategies.